ANALYSIS OF STUDENTS' QUESTIONING SKILLS TO CORRECT MISCONCEPTIONS RELATED TO UNDERSTANDING TEMPERATURE AND HEAT MATERIALS - Munawaroh, Afifah Al; Faninda Novika Pertiwi; Udomsak Kitthawee (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
This study aims to analyze the questioning ability of grade VII students in an effort to correct misconceptions on temperature and heat materials. The ability to ask questions is an important skill in the learning process, because the right questions can help students dig deeper into understanding and identify and correct their misconceptions. This study uses a qualitative descriptive approach with the subject of grade VII students in one of the junior high schools based on Islamic boarding schools in Ponorogo. Data was obtained through tests, interviews, and document analysis in the form of student question notes during the learning process. The results of the study show that most students still have difficulty asking exploratory and critical questions related to the concept of temperature and heat. However, through targeted guidance from teachers, the quality of the questions. From the questions asked by students on the material on temperature and heat, it can be an indicator of misconceptions because by asking questions, students have constructed their own thoughts, making them more curious and satisfying that curiosity through their ability to ask questions. this research connects the two showing how questioning can be a diagnostic and corrective tool to address students’ conceptual misunderstandings. This research is important because many students still hold misconceptions about temperature and heat, while their questioning skills remain low, preventing these errors from being revealed. By analyzing students’ questions, this study provides an effective way for teachers to diagnose misunderstandings early and improve science learning quality.